Expert vs novice collaborative heuristic evaluation (CHE) of a smartphone app for cultural heritage sites - Mohd Kamal, Othman; Ong, Lay Wan; Shaziti, Aman (Springer Nature, 2022)
This study was conducted to compare CHE between Human-Computer Interaction (HCI) experts and novices in evaluating the Smartphone app for the cultural heritage site. It uses the Smartphone Mobile Application heuRisTics (SMART), focusing on smartphone applications and traditional Nielsen heuristics, focusing on a wider range of interactive systems. Six experts and six novices used the severity rating scale to categorise the severity of the usability issues. These issues were mapped to both heuristics. The study found that experts and novice evaluators identified 19 and 14 usability issues, respectively, with ten as the same usability issues. However, these same usability issues have been rated differently. Although the t-test indicates no significant differences between experts and novices in their ratings for usability issues, these results nevertheless indicate the need for both evaluators in CHE to provide a more comprehensive perspective on the severity of the usability issues. Furthermore, the mapping of the usability issues for Nielsen and SMART heuristics concluded that more issues with the smartphone app could be addressed through smartphone-specific heuristics than general heuristics, indicating a better tool for heuristic evaluation of the smartphone app. This study also provides new insight into the required number of evaluators needed for CHE.